Parental Guidance as a Determinant of Academic Achievement of Adolescent Learners in Public Primary Schools in Gem Sub-County, Kenya - Owuor, Naomi Odira (JOOUST, 2022)
Academic achievement in most public primary schools in rural areas has remained below average in Kenya according to Kenya National Examinations Council results for many years. Every year parents and guardians have expected their adolescent children to achieve better marks at the end of their primary education. However parental support plays a vital role with respect to the way the adolescent learners conduct themselves in relation to academic achievement and parents in Gem Sub-County have been observed to show minimal parental concern in matters related to academic performance of adolescents. The study therefore sought to establish parental guidance as a determinant of academic achievement of adolescent learners in public primary schools of Gem Sub County, Kenya. Study objectives were; to determine the relationship between Parental Cognitive Support and Adolescent Learners’ Academic achievement, to find out the relationship between Parental Behavioural Support and Adolescent Learners’ Academic Achievement, to identify the relationship between Parental Social Support and Adolescent Learners’ Academic Achievement and to investigate the relationship between Parental Emotional Support and Adolescent Learner’s Academic Achievement. The study adopted mixed method research approach where concurrent triangulation design was used. Vygotsky Sociocultural theory was used to inform this study. Target population comprised of 119 public primary schools and 22,665 learners from upper primary. Sample size of 377 learners, 36 guidance and counselling teachers, 36 parents and 1QASO participated in the study. Simple random and purposive and saturation sampling techniques were used to select respondents. Questionnaires and interview schedule were used to collect data. Validity of research instrument was achieved by use of expert judgment from School of Education, Department of Educational Psychology from Jaramogi Oginga Odinga University of Science and Technology while split half technique was used to determine the reliability of the questionnaires and a value of r=0.905 was reported. Data was analyzed quantitatively using descriptive statistics and inferential statistics (T-Test) while qualitative data was analyzed using thematic approach. Study results were presented in frequency tables, graphs, charts and percentages. Findings of the present study revealed that parental support greatly influenced academic performance of adolescent learners at p < 0.05. Findings of the present study are considered useful to the Ministry of Education, Policy makers, education stakeholders and head teachers to enlighten parents on importance of providing parental guidance to their children at adolescence stage in order to enhance academic performance in primary schools. Guidance and counseling teachers should constantly make follow-ups to ensure every adolescent learner in school receives the required parental support for better academic performance.